Modelling Passengers’ Arrivals at Public Transport Stops - Janosikova, Ludmila; Slavik, Martin (Communications - Scientific letters of the University of Zilina, 2015)
The paper presents statistical exploration of passengers’ arrivals at bus stops in urban public transport. First, it describes the methodology which is applied on the urban public transport system where the following conditions are met: (i) passengers are familiar with the timetables, (ii) the vehicles run on time, and (iii) the capacity of the vehicles is sufficient. The methodology is demonstrated on the urban public transport in Zilina, Slovak Republic. The correlation analysis reveals that there is a correlation between the waiting time and headway. The relationship between these variables can be described by a linear function or better by a logarithmic function. The Kolmogorov-Smirnov and the chi-square tests accept the hypothesis that the Gumbel minimum distribution fits for modelling passengers’ arrivals rates. The proposed models are helpful in public transport planning.